Modelling last glacial cycle ice dynamics in the Alps - Seguinot, Julien; id_orcid:0 000-0002-5315-0761; Ivy-Ochs, Susan; Jouvet, Guillaume; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Funk, Martin; Preusser, Frank (Copernicus, 2018)
The European Alps, the cradle of pioneering glacial studies, are one of the regions where geological markers of past glaciations are most abundant and well-studied. Such conditions make the region ideal for testing numerical glacier models based on simplified ice flow physics against field-based reconstructions and vice versa. Here, we use the Parallel Ice Sheet Model (PISM) to model the entire last glacial cycle (120–0ka) in the Alps, using horizontal resolutions of 2 and 1km. Climate forcing is derived using two sources: present-day climate data from WorldClim and the ERA-Interim reanalysis; time-dependent temperature offsets from multiple palaeo-climate proxies. Among the latter, only the European Project for Ice Coring in Antarctica (EPICA) ice core record yields glaciation during marine oxygen isotope stages 4 (69–62ka) and 2 (34–18ka). This is spatially and temporally consistent with the geological reconstructions, while the other records used result in excessive early glacial cycle ice cover and a late Last Glacial Maximum. Despite the low variability of this Antarctic-based climate forcing, our simulation depicts a highly dynamic ice sheet, showing that Alpine glaciers may have advanced many times over the foreland during the last glacial cycle. Ice flow patterns during peak glaciation are largely governed by subglacial topography but include occasional transfluences through the mountain passes. Modelled maximum ice surface is on average 861m higher than observed trimline elevations in the upper Rhône Valley, yet our simulation predicts little erosion at high elevation due to cold-based ice. Finally, despite the uniform climate forcing, differences in glacier catchment hypsometry produce a time-transgressive Last Glacial Maximum advance, with some glaciers reaching their modelled maximum extent as early as 27ka and others as late as 21ka. ISSN:1994-0416 ISSN:1994-0424